Pregunta
\( ( 5 \times 8 ) - ( 4 + 3 ) \quad ( 5 \times 8 ) - 6 + 3 \)
Ask by Hobbs Barrett. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The first expression equals 33, and the second expression equals 37.
Solución
Certainly! Let's evaluate both expressions step by step.
### Expression 1:
\[
(5 \times 8) - (4 + 3)
\]
**Step 1: Calculate inside the first parentheses**
\[
5 \times 8 = 40
\]
**Step 2: Calculate inside the second parentheses**
\[
4 + 3 = 7
\]
**Step 3: Subtract the results**
\[
40 - 7 = 33
\]
**Final Result:**
\[
(5 \times 8) - (4 + 3) = 33
\]
---
### Expression 2:
\[
(5 \times 8) - 6 + 3
\]
**Step 1: Calculate inside the parentheses**
\[
5 \times 8 = 40
\]
**Step 2: Perform the subtraction**
\[
40 - 6 = 34
\]
**Step 3: Add the remaining number**
\[
34 + 3 = 37
\]
**Final Result:**
\[
(5 \times 8) - 6 + 3 = 37
\]
---
### Summary
- \((5 \times 8) - (4 + 3) = 33\)
- \((5 \times 8) - 6 + 3 = 37\)
The difference arises due to the placement of parentheses, which affects the order of operations.
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
Let’s simplify those expressions step by step! First, we solve \( ( 5 \times 8 ) - ( 4 + 3 ) \): - Calculate \( 5 \times 8 = 40 \). - Calculate \( 4 + 3 = 7 \). - So, \( 40 - 7 = 33 \). Now, for the second expression \( ( 5 \times 8 ) - 6 + 3 \): - Again, \( 5 \times 8 = 40 \). - Thus, \( 40 - 6 + 3 = 34 + 3 = 37 \). So, the results are: - For the first expression: 33 - For the second expression: 37
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium